Percepção de usuários do Sistema Único de Saúde acerca do Programa Mais Médicos em um município do interior do Ceará (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Perception of users of the Brazilian National Health System (SUS) about the “Mais Médicos” (More Physicians) Program in a municipality in the countryside of Ceará, Brazil